2020
DOI: 10.1159/000510342
|View full text |Cite
|
Sign up to set email alerts
|

Expression of <b><i>AdipoR1</i></b> and <b><i>AdipoR2</i></b> and Serum Level of Adiponectin in Gastric Cancer

Abstract: Background: Cancer is one of the major causes of death worldwide and the third leading cause of death in Iran. One of the proteins that are considered having anticancer effects is the adiponectin hormone. Adiponectin leads to programmed cell death, prevents cell growth and proliferation, and increases the expression levels of BCL2. Aim: The aim of this study was to assay the expression of adiponectin receptors (AdipoR1 and AdipoR2) genes in gastric cancer patients. Materials and Methods: In this case-control s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Adiponectin receptors (ADIPORs) are membrane proteins implicated in the control of glucose and lipid metabolism. Different studies have determined the incidence relationship of certain cancers with polymorphisms of the genes that code for ADIPORs [ 152 , 153 , 154 ]. Moreover, several studies have demonstrated the efficiency of ADIPORs agonists to induce cell death in cancer cells, such as (2-(4-Benzoylphenoxy)-N-[1-(phenylmethyl)-4-piperidinyl]-acetamide) in cholangiocarcinoma [ 155 ], ADP355 in prostate cancer [ 156 ] or AdipoRon with pancreatic cancer cells [ 157 ].…”
Section: Enzymes Of Ceramide Metabolismmentioning
confidence: 99%
“…Adiponectin receptors (ADIPORs) are membrane proteins implicated in the control of glucose and lipid metabolism. Different studies have determined the incidence relationship of certain cancers with polymorphisms of the genes that code for ADIPORs [ 152 , 153 , 154 ]. Moreover, several studies have demonstrated the efficiency of ADIPORs agonists to induce cell death in cancer cells, such as (2-(4-Benzoylphenoxy)-N-[1-(phenylmethyl)-4-piperidinyl]-acetamide) in cholangiocarcinoma [ 155 ], ADP355 in prostate cancer [ 156 ] or AdipoRon with pancreatic cancer cells [ 157 ].…”
Section: Enzymes Of Ceramide Metabolismmentioning
confidence: 99%
“…The dysregulation of ADIPOR1/2 is observed in various cancers. A study reported that both ADIPOR1 and ADIPOR2 are highly increased in gastric cancer samples from patients in Iran ( 8 ). Adrenal cancers are also associated with ADIPOR1 and ADIPOR2.…”
Section: Introductionmentioning
confidence: 99%
“…19 In recent years, it has been found that ADIPOR1 also plays an important role in tumorigenesis, invasion, and metastasis. 20 - 23 As for ADIPOR1 and liver cancer, it reported that overexpressed miR-221 promoted epithelial-mesenchymal transition (EMT) in hepatocellular carcinoma by targeting ADIPOR1, 24 and low expression of ADIPOR1 was associated with increased risk of recurrence and death in patients with liver cancer. 25 In this study, we identified ADIPOR1 as a prognostic marker for SBRT in patients with liver cancer through clinical information, high-throughput sequencing and qPCR analysis.…”
Section: Introductionmentioning
confidence: 99%